Penerapan Fuzzy Mamdani Dalam Pemilihan Murid Teladan Pada Sekolah Paud Harmony Kotawaringin Timur - Puji Susanti; Sherly Mudrika Bahri (Journal of Information System Research (JOSH), 2021)
Fuzzy logic is a method used to map an input space into an output space. Fuzzy logic theory is known as fuzzy set (fuzzy set). One of the applications of Fuzzy is used to facilitate the selection of exemplary students. Previously, this school had difficulty in reviewing students' achievements and examples. To solve this problem, a Decision Support System (DSS) was applied using the Fuzzy Mamdani method. Fuzzy method is more effective than manual selection because it doesn't take long. This study will discuss the use of the fuzzy mamdani logic method in determining the category of (i) model or non-exemplary students at HARMONY Sampit PAUD School, East Kotawaringin. The problem to be solved is how to determine students (i) Exemplary or Not Exemplary in Study Group B by using three input variables, namely Report Card Value, Attendance and Attitude Value. The first step in solving the problem in determining the student (i) model or not using the fuzzy mamdani method is to determine the input and output variables which are firm sets. The second step is to change the input variables into fuzzy sets with the fuzzification process, then the third step is processing the fuzzy set data. And the last or fourth step is to change the output into a firm set by defuzzification with the centroid method, so that the desired results will be obtained in the output variable. The results of the calculation using the fuzzy mamdani method for the variable value of report cards 4, the variable value of attendance value 2, the value of attitude 4 is 3.5